Allamanda karstica (Apocynaceae), a new species from limestone outcrops in central Brazil - Marcusso, Gabriel Mendes; Lombardi, Julio Antonio; Forzza, Rafaela Campostrini (Phytotaxa, 2026)
Allamanda is a Neotropical genus of Apocynaceae consisting of shrubs, treelets or scandent plants usually with verticillate leaves and intrapetiolar colleters, showy flowers, foliaceous sepals, corolla tubular-campanulate, usually yellow or sometimes purple, violet, lilac to red, cream, salmon, and dehiscent capsular fruits characterized by echinate, smooth or muricate surfaces. During field expeditions in the limestone outcrops of Tocantins State in central Brazil this new species was discovered. Herein we describe Allamanda karstica, a unique species in the genus due to its smooth fruit surface with spines limited to dehiscing fissures. Color photographs, a distribution map, preliminary conservation assessment, morphological comparisons with the related species, as well as an identification key to Allamanda occurring in limestone outcrops of Brazil are presented herein.